Organizing Intellectual Competitions of Students in Universities: Forms and Areas for Improvement - Zaiets, S. V.; Yudina, S. P. (Statistics of Ukraine, 2020)
The article outlines the tasks facing higher education institutions in the context of digitalization and acceleration of the knowledge updating process, which are aimed at creating a sustainable system for acquiring competencies, entrepreneurial skills and civic duties among students, teachers and employees. Performance indicators of all-Ukrainian student Olympiads, All-Ukrainian competitions of research works in Ukraine in 2009–2019 analyzed, to find out the patterns of organization of various intellectual competitions of students and their regional features. The factors contributing in the growth of participation of students from higher education institutions in these events were determined. It is indicated that the share of new organizational forms of Olympiads such as business games, blitz tournaments, solving situational problems, performing essay tasks, practical tours with employers’ support and participation is increasing. The results of a survey of 200 higher education institutions on student participation in international competitions held abroad and their prizes in 2015 and 2019 are presented. The tendencies of student involvement in international competitions abroad, in international, all-Ukrainian conferences, seminars for students and young researchers are outlined. Areas for improvement of intellectual competitions of students with account to priorities of modernization and technological development of the Ukrainian economy, employer needs and social demands are formulated. It is proposed to introduce comprehensive forms and methods for stimulating students’ interest in learning and self-development, obtaining high-quality education through intellectual games such as scholarship, grant or competitive ones. Evidence is given of the need to reform the nomenclature of specialties with highlighting the disciplines or the modules of disciplines in which the following types of all-Ukrainian intellectual competitions of students should be held: subject Olympiads, competitions of student research works, professional competitions.